The Effect of Different Composition of Aren Sugars (Arenga pinnata) on the Quality of Tilapia (Oreochromis niloticus) “Bekasam - Hutabarat, Sarima Ruth; Sari, N. Ira; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The study was aimed to determine the effect of the different composition of aren sugars (Arenga pinnata) on the quality of tilapia (Oreochromis niloticus) Bekasam. The research was using the experimental method and designed as the the Completely Randomized Design (CRD). The treatment conducted was addition of aren sugar at different compositions, namely: 40% rice flour without aren sugar added, 3% and 5% aren sugar added. Parameter used were organoleptic value, pH, total lactic acid, and total plate count. The result was showing that the bekasam added with 40% rice flour 5% sugar aren was producing the best quality of bekasam. The best bekasam was indicated by the highest organoleptic quality with the value of appearance 7.2 with the characteristic of interesting, clean, brownish color; the value of texture 6.36 with the characteristics of chewy, solid, and compact; the value of aroma 7.9 with specific characteristic of fresh and typically bekasam; and the value of taste 6.92 with the characteristic of acid, salted, typically bekasam and slightly tasted of palm sugar, pH value of bekasam was 4.6,tpc of bekasam 2,6 14x103